2005
DOI: 10.1136/gut.2004.062398
|View full text |Cite
|
Sign up to set email alerts
|

Chronic liver injury in rats and humans upregulates the novel enzyme angiotensin converting enzyme 2

Abstract: Background: Angiotensin converting enzyme (ACE) 2 is a recently identified homologue of ACE that may counterregulate the actions of angiotensin (Ang) II by facilitating its breakdown to Ang 1-7. The reninangiotensin system (RAS) has been implicated in the pathogenesis of cirrhosis but the role of ACE2 in liver disease is not known. Aims: This study examined the effects of liver injury on ACE2 expression and activity in experimental hepatic fibrosis and human cirrhosis, and the effects of Ang 1-7 on vascular to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
318
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(353 citation statements)
references
References 26 publications
16
318
0
8
Order By: Relevance
“…There is considerable animal model data supporting an antifibrotic role for the ACE2/Ang (1-7)-MAS axis of the RAS in hepatic fibrosis [1][2][3][6][7][8] . Therefore, we speculate that the RAS may be shifted away from profibrotic responses towards antifibrotic responses by the upregulation of a novel ACE2/Ang (1-7)-MAS axis in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable animal model data supporting an antifibrotic role for the ACE2/Ang (1-7)-MAS axis of the RAS in hepatic fibrosis [1][2][3][6][7][8] . Therefore, we speculate that the RAS may be shifted away from profibrotic responses towards antifibrotic responses by the upregulation of a novel ACE2/Ang (1-7)-MAS axis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…We presume that ACE2 amplification stimulates Ang II degradation and that a decrease in ACE lessens the formation of Ang II. Moreover, Ang (1-7) could be converted to the inactive peptide fragment Ang (1)(2)(3)(4)(5) by the degradation of ACE, and ARBs are known to promote Ang (1-7) expression levels [26] . Furthermore, a decrease of ACE expression levels could offer additional protective effects for hepatic fibrosis through the increased expression of MAS levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paizis et al [14] demonstrated that in both BDL rat and human livers there was an increased ACE2 expression and activity that might facilitate the conversion of Ang Ⅱ to Ang-(1-7). Pereira et al [12] demonstrated that the progression of liver dysfunction in BDL rats was characterized by marked changes in Ang-(1-7) and Ang Ⅱ levels and the overall activation of circulating RAS was associated with the progression of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…While the ACE-Ang Ⅱ-AT1 receptor arm contributes to liver tissue injury and fibrosis [6] and the maintenance of basal vascular tonus in non-compensated cirrhosis [11] , the activation of the ACE2-Ang-(1-7)-Mas arm exerts antifibrotic actions [6,12,13] . In addition, it has been speculated that this counter-regulatory arm also has a role in the arterial vasodilation in liver cirrhosis [14] . In this regard, we have recently shown that chronic treatment with propranolol in cirrhotic patients was characterized by marked changes in the precursors of the RAS cascade (renin and Ang Ⅰ), with repercussions on the 2 main RAS components, Ang Ⅱ and Ang-(1-7), in the splanchnic and peripheral circulations [15] .…”
Section: Introductionmentioning
confidence: 99%